2021
DOI: 10.1126/sciadv.abf0452
|View full text |Cite
|
Sign up to set email alerts
|

On secondary atomization and blockage of surrogate cough droplets in single- and multilayer face masks

Abstract: Face masks prevent transmission of infectious respiratory diseases by blocking large droplets and aerosols during exhalation or inhalation. While three-layer masks are generally advised, many commonly available or makeshift masks contain single or double layers. Using carefully designed experiments involving high-speed imaging along with physics-based analysis, we show that high-momentum, large-sized (>250 micrometer) surrogate cough droplets can penetrate single- or double-layer mask material to a signific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 55 publications
4
78
0
Order By: Relevance
“…The movies were made using Kdenlive software. Experimental methodology is similar to Sharma et al 32 …”
Section: Experimental Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…The movies were made using Kdenlive software. Experimental methodology is similar to Sharma et al 32 …”
Section: Experimental Methodologymentioning
confidence: 99%
“…Fluid dynamically droplet impact on a facemask is similar to impingement on porous networks like metallic wire meshes, 19–25 fibers, 26–30 and textiles. 31 Sharma et al 32 focused on the effect of the number of layers present in a surgical mask and showed that the number of cough droplets penetrating through the mask is significantly reduced with each additional mask layer. The experiments were performed for droplet sizes of ∼300–600 μ m and velocity range of 2–10 m/s (Ref.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations